Energy and Resource Efficiency in Aluminium Die Casting - Heinemann, Tim (Sustainable Production, Life Cycle Engineering and Management, 2016)
This monograph provides a field-proven approach to analyze industrial production with a cross-company scope as well as regarding all hierarchical system levels of manufacturing enterprises. The book exemplifies this approach in the context of aluminum  die casting, and presents a set of measures which allow a 30 percent energy reduction along the value chain. The target audience primarily comprises researchers and experts in the field but the book may also be beneficial for graduate students.